2005
DOI: 10.2460/ajvr.2005.66.93
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glucose tolerance and intestinal luminal membrane glucose transporter function in horses with equine motor neuron disease

Abstract: Data suggest that the decreased plasma glucose curve obtained in horses with EMND during OGTTs (compared with control horses) is a result of overall enhanced glucose metabolism or abnormalities in the facilitated glucose transporters; definitive identification of the underlying mechanisms could aid in the development of appropriate treatments of EMND in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…The values of MUP variables had characteristics corresponding with neuropathic MUPs according to definitions determined in former studies in warmblood horses (2,59,60).…”
Section: Emg Analysismentioning
confidence: 99%
“…The values of MUP variables had characteristics corresponding with neuropathic MUPs according to definitions determined in former studies in warmblood horses (2,59,60).…”
Section: Emg Analysismentioning
confidence: 99%
“…In 7 out of 12 cases, an oral glucose tolerance test (according to Benders et al 2005) was performed with poor glucose absorption shown in only 2 cases. In addition, in 6 out of 12 cases gastro-duodenoscopyassisted biopsies taken from the proximal duodenum were available for histopathology revealing predominantly very mild lymphocytic-plasmacytic enteritis.…”
Section: Resultsmentioning
confidence: 99%
“…57 Techniques for quantitative analysis of motor action potentials have been published, 59 and results are abnormal in horses with EMND. 60 Regardless of the EMG technique used, abnormal results are nonspecific as to cause, suggesting only denervation or myopathy. 56 GLUCOSE ABSORPTION/METABOLISM Oral glucose tolerance tests in horses with EMND were abnormal in approximately 50% of reported cases whereas results of oral xylose absorption tests were normal or slightly low.…”
Section: Needle Electromyographymentioning
confidence: 99%
“…56 GLUCOSE ABSORPTION/METABOLISM Oral glucose tolerance tests in horses with EMND were abnormal in approximately 50% of reported cases whereas results of oral xylose absorption tests were normal or slightly low. 40,43,60 Plasma glucose curves were lower than reference range in 6/8 horses given oral glucose and peak glucose concentrations were below normal range in 2/6 horses given IV glucose. 60 On the basis of hyperglycemic clamp results in these horses, it was suggested that increased glucose metabolism, rather than reduced intestinal absorption, was the cause of abnormal oral glucose tolerance in horses with EMND.…”
Section: Needle Electromyographymentioning
confidence: 99%
See 1 more Smart Citation